2017
DOI: 10.21037/jtd.2017.07.07
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA260-specific siRNA targeting IL28RA gene inhibit cardiomyocytes hypoxic/reoxygenation injury

Abstract: Background:The interleukin 28 receptor alpha (IL28RA) gene was indicated to be associated with apoptosis.However, it was not clear whether long non-coding RNA 260 (lncRNA 260)-specific siRNA targeting IL28RA gene could inhibit hypoxic reoxygenation (H/R) cardiomyocytes injury or not. To explore the mechanisms underlying the protective effects of lncRNA260-specific siRNA-mediated inhibition of IL28RA from H/R injury in cardiomyocytes, the current research was performed.Methods: The primary neonatal rat cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our previous studies have shown that downregulation of lncRNA260 regulates IL28RA and activates the JAK-STAT and PI3K/AKT signaling pathways, and this phenomenon improves the injury of hypoxic cardiomyocytes in rats [ 15 ]. This effect is thought to be related to the reduction in IL28RAV2.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that downregulation of lncRNA260 regulates IL28RA and activates the JAK-STAT and PI3K/AKT signaling pathways, and this phenomenon improves the injury of hypoxic cardiomyocytes in rats [ 15 ]. This effect is thought to be related to the reduction in IL28RAV2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PI3KCG is a primary downstream gene regulated by IL28RA. Knockdown of IL28RA promotes cell proliferation and inhibits apoptosis by activating PI3K/AKT signaling pathways [52]. Thus, lncRNA260, as a guiding molecule, participates in the pathological process of myocardial apoptosis associated with H/R injury by regulating the transcription of IL28RA.…”
Section: Lncrna260mentioning
confidence: 99%
“…It was suggested that lncRNA260 might regulate IL28RA gene through trans effect and participate in the signal transmission process in the post AMI process. Our previous studies have shown that down-regulation of lncRNA260 regulates IL28RA and activates the JAK-STAT and PI3K/AKT signaling pathways, thus improving the injury of hypoxic cardiomyocytes in rats [13] , which is thought to be related to the reduction of IL28RAV2. Therefore, we speculate that lncRNA260-speci c siRNA could reduce the expression of IL28RAV2 gene, activate JAK-STAT and PI3K/AKT signaling pathways, promote the polarization of macrophages to M2-type, inhibit in ammatory response, and thus achieve certain biological effects.…”
Section: Introductionmentioning
confidence: 96%